A restorative approach to family violence : feminist kin-making - Pennell, Joan, 1949- (New York, NY : Routledge, 2023)
"A Restorative Approach to Family Violence looks back at an early and successful demonstration of a family-and-culturally-based model to stop severe family violence. This conferencing model, called family group decision making, was applied by three diverse Canadian communities-Inuit, rural, and urban-to the benefit of child and adult family members. Narrative inquiry identifies how engaging the family and relatives resets the narrative from misrecognition to recognition of their competence and caring. Family violence poses some of the most long-term and controversial questions in restorative justice. Should we use a restorative approach to stop gendered and intergenerational harm? Or will bringing together those who have been harmed, those causing harm, and their supporters only incite more violence? Underlying these questions is a profound distrust of families and their cultural networks. This distrust has stalled turning away from carceral interventions that particularly harm minoritized communities. Moving forward in time, the volume identifies blocks to trusting families and their cultural networks and means of circumventing these blocks. The book offers a theory of feminist kin-making to comprehend the restorative process and gives practical guidance to restorative participants, practitioners, policy makers, and researchers"--
Keywords: Family violence; Family violence -- Prevention; SOCIAL SCIENCE / Criminology